1992
DOI: 10.1288/00005537-199210000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of unilateral and bilateral nasal obstruction on snoring and sleep apnea

Abstract: The purpose of this study was to compare apnea and snoring in patients with different patterns of nasal resistance: normal, high unilateral, and high bilateral. The authors examined 683 unselected patients referred for evaluation of snoring and possible sleep apnea. All patients had determination of nasal resistance (performed during wakefulness in the seated posture) and nocturnal polysomnography including quantitative measurement of snoring. Analysis of variance showed no significant difference in apnea and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
1
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 11 publications
0
64
1
4
Order By: Relevance
“…Many studies show that, in the awake state, nasal obstruction is an independent risk factor for OSAS 4 . These results have been contradicted by other studies, which found differences between apnea and snoring patients with nasal resistance 5 . A similar study measuring supine nasal resistance failed to find any correlation with sleep disturbance indices.…”
Section: Introductioncontrasting
confidence: 68%
“…Many studies show that, in the awake state, nasal obstruction is an independent risk factor for OSAS 4 . These results have been contradicted by other studies, which found differences between apnea and snoring patients with nasal resistance 5 . A similar study measuring supine nasal resistance failed to find any correlation with sleep disturbance indices.…”
Section: Introductioncontrasting
confidence: 68%
“…Using postnasal rhinomanometry in 683 patients, MILJETEIG et al [11] found no statistically significant relationships between nasal resistance and either snoring or OSAS. These findings are different from those in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, direct comparison of the two studies is difficult for several reasons. 1) MILJETEIG et al [11] compared only the snoring index and AHI between patients with normal and abnormal nasal resistance, without performing regression analysis. 2) The method for nasal resistance measurement was not the same in the two studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may still help to relieve airway obstruction but usually has a very positive effect on improving the quality of life and CPAP tolerance in OSA patients (21,22). (13) reported on 14 patients with allergic rhinitis and 7 controls.…”
Section: Effects Of Nasal Anatomical Abnormalities On Osamentioning
confidence: 99%